Pengembangan pembelajaran permainan bolavoli pada mahasiswa - Destriani, Destriani; Destriana, Destriana; Switri, Endang; Yusfi, Herri (Universitas Nusantara PGRI Kediri, 2019)
This study aimed to produce the development of proper volleyball games learning for students. The research method used in this study was Research and Development. The development steps were done by using Analysis, Design, Development, Implementation and Evaluation which were often referred to the ADDIE model. The subjects in this study were the students of Physical and Health Education Study Program of Teacher Training and Education Faculty of Sriwijaya University. The results of this study indicated that overall the development of volleyball games learning is feasible to be used. The data analysis technique used was quantitative descriptive analysis. The results of this study included the development of facilities, infrastructure, and rules of volleyball games. In the facilities aspect was by changing the height of the net to 2.15 meters. In the infrastructure aspect modified the size of the field to be 16x9 meters. While in the rules of the game aspect combined female and male students. The feasibility of the development was obtained from the results of the assessment of material experts which were obtained an average of 80.67% included in the good category while the effectiveness was obtained from the learning outcomes of the implementation phase of students with the outcome on the psychomotor aspect was 77.08% included in the sufficient category. The implementation of this development research was that the educators could use as an alternative in teaching and could improve the students’ learning outcomes on psychomotor aspect.